Secreted protein, acidic and rich in cysteine (SPARC) expression in astrocytic tumour cells negatively correlates with proliferation, while vascular SPARC expression is associated with patient survival - Capper, David; Mittelbronn, M.; Goeppert, Benjamin; Meyermann, R.; Schittenhelm, J. (Neuropathology & applied neurobiology, 2010)
D. Capper, M. Mittelbronn, B. Goeppert, R. Meyermann and J. Schittenhelm (2010) Neuropathology and Applied Neurobiology36, 183-197 Secreted protein, acidic and rich in cysteine (SPARC) expression in astrocytic tumour cells negatively correlates with proliferation, while vascular SPARC expression is associated with patient survival Aims: Secreted protein, acidic and rich in cysteine (SPARC) is a regulator of cell-matrix interaction and has been associated with tumour stage and patient survival in various malignancies. As no large-scale study has yet been undertaken, we investigated human brain and astrocytomas for SPARC expression and associations with tumour grade, proliferation, vascular density and patient survival. Methods: A spectrum of 188 WHO grade I-IV astrocytic tumours and 24 autopsy cases were studied by immunohistochemistry for SPARC, MIB-1 proliferation index and CD31-positive vessels. SPARC protein expression was confirmed by quantitative real-time polymerase chain reaction and Western blot in 13 cases. Results: In normal brain, SPARC is expressed in cortical marginal glia, cerebellar Bergmann glia and focally in white matter but is absent in neurones or vessels. High SPARC expression levels in the cytoplasm of astrocytic tumour cells decreased with the grade of malignancy but showed an increase with grade of malignancy in tumour vessels. SPARC negatively correlated with tumour proliferation but not with vascular density. While cytoplasmic SPARC staining was not associated with survival, vascular SPARC showed a significant association in the group of grade II-IV tumours (P = 0.02) and also in grade II astrocytomas alone (P = 0.01) with vascular SPARC associated with worse prognosis. Conclusions: SPARC is highly expressed in astrocytomas and decreases with tumour progression. We confirm an association of increased SPARC expression and decreased proliferation. While there is no association between the level of SPARC in the tumour cells and patient survival, increased tumour vascular SPARC expression is associated with decreased patient survival.